The last full measure [videorecording (DVD)] - Robinson, Todd, 1958-; Stan, Sebastian, 1982-; Plummer, Christopher; Hurt, William; Jackson, Samuel L.; Fonda, Peter, 1940-2019; Hamilton, Lisa Gay, 1964-; Ladd, Diane; Harris, Ed, 1950-; Madigan, Amy (Lions Gate, 2020)
The true story of William Pitsenbarger, an Air Force medic who saved more than sixty men in one of the bleakest battles of the Vietnam War. Presented the chance to escape on the last helicopter, Pitsenbarger stayed behind to save and defend his comrade in arms. Twenty years later, Pitsenbarger's fellow soldiers and father seek the help of investigator Scott Huffman and other surviving veterans to finally secure him The Congressional Medal of Honor he deserved.